The influences of shading, fruit thinning, plant growth promoter and inhibitor on Malaysian wax apple (syzygium samarangense) fruit development and quality / Abdullah Issa Alebidi - Abdullah, Issa Alebidi (2014)

(untitled)
Currently, there are limited documented reports on effects of shading and thinning horticultural practice and plant growth regulators (PGRs) on wax apple (Syzygium samarangense) var. ‘jambu air madu’ growth, development, and quality. PGRs and horticultural practices are important means used in fruit production throughout the world. These means regulate several physiological and biochemical aspects of growth, development, yield and nutritional quality of fruits. In this study, five experiments were conducted to improve the potential of wax apple fruits as follows; applications of gibberellic acid (GA3) (30, 60 and 90 ppm) applied via xylem injection (an innovative method), application of naphthalene acetic acid (NAA) (30, 60 and 90 ppm) through fruit swabbing method, application of abscisic acid (ABA) (50, 100, 150 ppm) applied through swabbing method at the 4th ,5th ,6th week of fruit development, fruit thinning regimes at 10 fruits/branch (F/B), 15 F/B, 20 F/B and control treatment (un-thinned fruit), and lastly shading branches treatments at 50%, 70% levels shade and without shading (control). Various physiological and biochemical parameters were monitored during successive seasons of fruit growth between 2010 to 2012 at commercial farm located in Bating, Selangor, Malaysia. The results showed that thinning treatment (at 10 F/B and 15 F/B) enhanced fruit growth, increased fruit length, diameter, and weight. The highest fruit weight was observed in 10F/B treatment followed by 15 F/B treatment whereas the lowest weight was recorded in the control treatment. However, fruit thinning treatments had negative impacts on final yield. The highest yield was obtained in 20 fruits/branch treatment followed by the control treatment and 15 F/B treatments whereas the lowest yield was recorded in 10 F/B treatment. Regarding fruit quality parameters, thinning at 10 F/B and 15 F/B increased slightly fruit juice percentage, pH, total soluble solids (TSS), inverted sugars, fructose, sugar acid ratio (TSS/TA), total flavonoids, total phenol, K+ content and anthocyanin content in fruits. On the other hand, thinning treatment at 10 F/B and 15 F/B decreased vii titratable acidity (TA) in fruits. In addition, thinning did not significantly affect leaf chlorophyll content (SPAD) value. The effect of shading experiment on wax apple fruit growth and quality showed that; all shading treatments (50% and 70% shade) decreased significantly pH, TSS, inverted sugars, and fructose, sugar acid ratio (TSS/TA), total flavonoids, total phenol, K+ content and anthocyanin content and increased TA in the fruits. Although, there was no significant difference among all shading treatments in total phenol, the shading treatment had slightly non-significant less phenol content when compared to the control. Shading treatment adversely affected fruit growth, weight, bud drop, fruit drop, and yield. The highest weight was recorded in the control treatment whereas the lowest weight was observed in 70% shading treatment. All shading treatments increased significantly the bud and fruit drop when compared to the control treatment. The lowest branch yield observed in 70% shade treatment followed by 50% shade treatment. In addition, shading reduced slightly (non-significant) the SPAD value. The application of GA3 via xylem injection enhanced fruit growth, increased fruit length, diameter colour, and weight. GA3 also increased fruit set and reduced bud and fruit drop. With regard to fruit quality, the application of GA3 increased fruit juice percentage, pH, TSS, inverted sugars, fructose, TSS/TA ratio, total flavonoids, total phenol, K+, and anthocyanin content in the fruits. On the other hand, GA3 decreased TA in fruits, and did not affect SPAD value. Swabbing with NAA treatment enhanced fruit growth, fruit size, weight, and fruit set. NAA also reduced bud and fruit drop. NAA treatment increased TSS, inverted sugar, fructose, total phenol, total flavonoids, K+ and anthocyanin content in fruit, however, NAA treatment did not affect SPAD value. Swabbing fruit with ABA at relatively advance stage of fruit development, increased slightly fruit drop, but did not significantly affect yield, fruit size, and weight. In addition, all ABA treatments enhanced significantly anthocyanin accumulation in fruit. ABA at 150 ppm increased TSS, inverted sugar, fructose, TSS/TA ratios, and pH, and viii reduced TA, but did not affect significantly K+, total phenols, and total flavonoids content in fruit. ABA treatments did not affect significantly the SPAD value. In conclusion, GA3 treatment via xylem injection at 90 ppm concentration, NAA swabbing treatment at 90 ppm concentration, ABA swabbing treatment at 150 ppm concentration, and fruit thinning treatments at 10F/B and 15 F/B levels resulted in better fruit quality parameters of wax apple fruits under field conditions. However, thinning treatment at 10F/B severely lowered the branch yield. Therefore, a good balance between fruit quality and yield should be taken into consideration in wax apple fruit commercial production. All shading treatment (50 and 70%) had negative effect on fruit development and quality. Thus, maintaining a good sunlight exposure for wax apple tree is essential to improve wax apple fruit quality and yield.